Integration of Child Protection and Social Protection for Child Victims of Violence in Indonesia - Nawangsari, Anna Sakreti; Susanty , Dessy; Setiawan , Yoel; Nugroho, Fentiny (Asean Social Work Journal, 2024)
Social protection (SP) programs for children who are victims of violence have been provided through Child Protection (CP) services, but there are still gaps in meeting the needs in a comprehensive and sustainable manner. This study aims to determine the quality of CP services and their integration with SP services for child victims of violence in Indonesia. Using a qualitative case study method, this study was conducted in 4 provinces and 10 districts/cities, 5 cases of child victims of violence, and a number of informants from parents of victims, and stakeholders in the regions who are responsible for the issue of child victims of violence. Using qualitative methods, the results of the study indicate that there is no integrated policy between CP and SP services for child victims of violence. The lack of integration of CP and SP   occurs both among institutions and within the Ministry that has the main tasks and related functions. In some policies related to SP in the form of social assistance under the social rehabilitation program, it is only intended for the poor, so that only children who are victims of violence and are poor can get this service. Integration of child protection and social protection is very important to create a comprehensive framework to address the needs of children who are victims of violence and their families. This paper recommends the integration of social protection and social protection programs by including violence against children as part of the poverty indicators.